Luxembourg : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Luxembourg. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the economic growth in Luxembourg reached 2.3 percent in 2017, above the European Union average, and was driven by net exports of financial services and private consumption. Growth is projected at 3.5 percent for 2018, with continued strong job creation, and a temporary slowdown in inflation. In 2017, buoyant corporate tax revenues contributed to a fiscal surplus of 1.4 percent of GDP. The full impact of 2016 tax reform, and a continued need for high public investment are expected to result in a small fiscal surplus over the medium-term.